Photothermally Triggered Cytosolic Drug Delivery via Endosome Disruption Using a Functionalized Reduced Graphene Oxide - Kim, Hyunwoo; Lee, Duhwan; Kim, Jinhwan; Kim, Tae-il; Kim, Won Jong (ACS nano, 2013)
Graphene oxide has unique physiochemical properties, showing great potential in biomedical applications. In the present work, functionalized reduced graphene oxide (PEG-BPEI-rGO) has been developed as a nanotemplate for photothermally triggered cytosolic drug delivery by inducing endosomal disruption and subsequent drug release. PEG-BPEI-rGO has the ability to load a greater amount of doxorubicin (DOX) than unreduced PEG-BPEI-GO via π–π and hydrophobic interactions, showing high water stability. Loaded DOX could be efficiently released by glutathione (GSH) and the photothermal effect of irradiated near IR (NIR) in test tubes as well as in cells. Importantly, PEG-BPEI-rGO/DOX complex was found to escape from endosomes after cellular uptake by photothermally induced endosomal disruption and the proton sponge effect, followed by GSH-induced DOX release into the cytosol. Finally, it was concluded that a greater cancer cell death efficacy was observed in PEG-BPEI-rGO/DOX complex-treated cells with NIR irradiation than those with no irradiation. This study demonstrated the development of the potential of a PEG-BPEI-rGO nanocarrier by photothermally triggered cytosolic drug delivery via endosomal disruption.